DEVELOPMENT OF A LOW-COST ROCKET STOVE TO IMPROVE COMBUSTION EFFICIENCY AND REDUCE SMOKE - Suflani, Suflani; Abdurrohman, Bagas; Mahesa, Alif Dava; Majammi, Maghfira Adjanni Ghifara; Agustin, Tia; Fitriani, Aulia; Fawwazni, Ahmad Hilmy; Fadhila, Khoirun Nisa; Wahyudi, Dichy; Rizki, Wahyu (International Journal of Engagement and Empowerment (IJE2), 2025)
His community service program aims to introduce and implement low-cost rocket stove technology in Cisaat Village, Tegal Village, as a solution to increase combustion efficiency and reduce the smoke problem often caused by burning waste in yards. This activity involved training in rocket stove construction, demonstrations of use, and mentoring the community in utilizing rocket stoves for their daily needs. The results of this activity indicate increased public awareness of the importance of using cleaner and more efficient technology. Furthermore, the use of rocket stoves has helped reduce smoke pollution levels in the surrounding environment and conserve fuel. This program is expected to have a sustainable positive impact on the health and well-being of the people of Cisaat Village, Tegal Village.